The Effect of COVID-19 Pandemic on the Energy Economics and Markets in Central and Eastern Europe (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
This reprint provides a comprehensive study of the impact of the COVID-19 pandemic on energy markets in Central and Eastern Europe. The COVID-19 pandemic has introduced significant changes and challenges to the energy sector worldwide. Sudden changes in energy demand, the need to adapt to new market and political conditions, and the increasing role of sustainable development and renewable energy sources have compelled the energy sector to seek innovative solutions. The motivation for writing this reprint was to understand these dynamic changes and their long-term consequences for the energy sector, economy, and society. The goal of this publication is to understand and analyze the impact of the COVID-19 pandemic on various aspects of the energy sector in Central and Eastern Europe, with a particular focus on Poland. The analysis covers several key aspects, such as innovative energy technologies in road transport in selected EU countries, changes in energy consumption, implementation of renewable energy technologies, CSR policies, employment in the energy sector, and risks associated with the pandemic. This publication is addressed to a broad audience, including researchers, students, policymakers, energy sector workers, and anyone interested in renewable energy and its role in sustainable development.